upaya penurunan nyeri pada pasien selulitisdi rsop dr. soeharso surakarta - Furlan, Feruni, Arina Maliya, S.Kep., M.Si.Med (2016)
Skin disease and subcutaneous diseases based on the prevalence of diseases in the Indonesia was ranked second after acute respiratory infections. One of themare cellulitis, cellulitis is a skin infection caused by the bacteria streptococcus and staphylococcus, with common complaints of pain. Pain due to inflammatory responses. Some pain management can be done to overcome the pain there are withgive the physiological position, immobilization ekstermitas with pain, hot and cold compress, guide imaginary, relaxation progressive distraction techniques, touch management, environmental management and colaboration analgesic drug. The main specific nursing strategies to improve comfort for patients who are experiencing pain, non pharmalogical. As we know that nurse don't have the authority to provide an analgesic.Scientific publication can understand nursing care for patients with a diagnosis of cellulitis cruris dextra tibia in Parang Kusumo class Orthopaedic Dr. R. Soeharso Surakarta Hospital. The method used is descriptive case study approach, namely by performing nursing care in patients with cellulitis, ranging from assessment, intervention, implementation and evaluation of nursing.After 3x24 hour nursing care for patients with cellulitis cruris dextra tibiaacute pain problems, sleep disturbances, activity intolerance, anxiety, ineffective airway clearance partially resolved andinterventions should be continued. The effect are showed nonpharmacological therapy in reducing pain scale.These five nursing problems resolved partially, thus requiring further treatment and cooperation with the other medical team, the patients and families are indispensable for the success of nursing care. The influence nonpharmacological therapy to decrease pain scale before and after the intervention. Recommended for patients with cellulitis as an act nursing treatment.